2012
DOI: 10.1007/s10508-012-9969-8
|View full text |Cite
|
Sign up to set email alerts
|

Sexting by High School Students: An Exploratory and Descriptive Study

Abstract: Recently, a phenomenon known as sexting, defined here as the transfer of sexually explicit photos via cell phone, has received substantial attention in the U.S. national media. To determine the current and potential future impact of sexting, more information about the behavior and the attitudes and beliefs surrounding it must be gathered, particularly as it relates to sexting by minors. The present study was designed to provide preliminary information about this phenomenon. Participants were 606 high school st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
127
3
20

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(165 citation statements)
references
References 22 publications
10
127
3
20
Order By: Relevance
“…However, other studies have indicated that males were more likely to engage in sexting than females (e.g. Delevi and Weisskirch 2013;Strassberg et al 2013). While females generally do appear to engage in sexting more often based on research findings to date, they have also been found to perceive sexting as more serious and as more likely to generate negative outcomes (e.g.…”
Section: Sexting Definitions and Prevalencementioning
confidence: 98%
“…However, other studies have indicated that males were more likely to engage in sexting than females (e.g. Delevi and Weisskirch 2013;Strassberg et al 2013). While females generally do appear to engage in sexting more often based on research findings to date, they have also been found to perceive sexting as more serious and as more likely to generate negative outcomes (e.g.…”
Section: Sexting Definitions and Prevalencementioning
confidence: 98%
“…A pesar de los innumerables beneficios que la evolución tecnológica ha reportado, son muchos los riesgos que pueden derivarse de su mal uso (Livingstone, Haddon, Görzig y Ólafsson, 2011;Muñoz-Miralles et al, 2016;Rial, Golpe, Gómez y Barreiro, 2015;Valkenburg y Peter, 2011). Existen trabajos que no solo alertan del uso abusivo de Internet por parte de los jóvenes (Blinka et al, 2015;Gencer y Koc, 2012) o el acceso incontrolado a contenidos pornográficos, violentos, racistas y sexistas, sino también de las numerosas prácticas de riesgo vinculadas al uso de la Red como el cyberbullying, el sexting o el grooming (Garaigordobil y Aliri, 2013;Strassberg, McKinnon, Sustaíta y Rullo, 2013;Wolak, Finkelhor y Mitchell, 2004). Algunos autores han llegado incluso a referirse a la posibilidad de desarrollar una adicción (Jorgenson, Hsiao y Yen, 2016;Young, 1996) o, cuando menos, un uso problemático de Internet (Anderson, Steen y Stavropoulos, 2016;Shapira et al, 2003).…”
Section: The Relationship Between Consumption Of Alcohol and Other Drunclassified
“…Studies of high school youth have suggested that sending nude or seminude photos is somewhat common, with 18% to 28% endorsing having done so. 7,8 The only study that included early adolescents found that between 1% and 2.5% (depending on the definition of sexting) of Internet users aged 10 to 17 reported having appeared in or created a sexually explicit photo. 9 However, methodologic limitations with this study (eg, interviewing teenagers on the phone with parents present, sampling methods that resulted in a largely white, upper socioeconomic status, 2-parent household sample) 7,8 make it challenging to draw firm conclusions.…”
mentioning
confidence: 99%
“…8 Other factors that may differentiate adolescents who sext versus those who do not include being nonheterosexual, white or African American, and older age. [6][7][8] Although research is limited regarding cognitive factors related to sexting, several studies have identified relationships between cognitions and other sex-related behaviors among adolescents. Reports of sexual intentions are related to sexual behaviors among youth with mental health problems, 11,12 but it is unknown whether teenagers with greater intentions to have sex engage in sexting.…”
mentioning
confidence: 99%